O ócio criativo e as inteligências múltiplas: dimensões de Domenico De Masi e Howard Gardner sobre o trabalho contemporâneo - Loureiro, Roberto de Oliveira (2009)
This thesis analyses the studies by Domenico de Masi and Howard Gardner, which respectively discusses Creative Leisure and Multiple Intelligences, concepts still scarcely considered in the business scenario that integrates into a new organizational model, transforming the relations between the employee and other people and the results of her own piece, more humanized, without losing focus on competitiveness, and sustainable growth, those being the targets of organizations which desire to survive the 21rst Century. The thesis also briefly discusses the evolutionary thought brought to light as of the main administrative theories as well as a critical analysis about working in a globalized world and how much the concept of work is different from employment